What is the clinical significance of a small pericardial effusion incidentally discovered on CT or echocardiogram?. Issue 11 (November 2017) - Over, Darrell R.; Hartsfield, Mark; Hartsfield, Miles; Rowell, Aaron
Abstract : EVIDENCE‐BASED ANSWER : The presence of a small asymptomatic pericardial effusion is associated with a 20% increase in mortality at 1 year and is more common in patients with heart failure with reduced ejection fraction, diabetes mellitus, renal disease, and malignancy. Most (94%) effusions resolve or remain unchanged by 1‐year follow‐up evaluation (SOR: B, retrospective cohort study). Followup evaluation of a pericardial effusion should be based primarily on the size of the effusion, symptoms, and other clinical features such as known associated disease or inflammatory markers. Idiopathic effusions of less than 1 cm generally do not need follow‐up (SOR: C, expert opinion).